Usefulness of Image Guidance in the Surgical Treatment of Petrous Apex Cholesterol Granuloma. (22nd October 2013) - Pietrantonio, A.; D'Andrea, G.; Famà, I.; Volpini, L.; Raco, A.; Barbara, M.
Abstract : The petrous apex is a pyramid-shaped structure, located medial to the inner ear and the intrapetrous segment of the internal carotid artery. Lesions of the petrous apex can be surgically treated through different surgical routes. Because of the important neurovascular structures located inside the temporal bone, anatomical 3D knowledge is paramount. For this reason, image-guided surgery could represent a useful tool. We report the case of a young woman who came to our observation for a trigeminal neuralgia due to a petrous apex cholesterol granuloma. The lesion was treated through the placement of a drainage tube via an infracochlear approach, with the aid of neuronavigation and intraoperative MRI. Preoperative CT scan images and intraoperative MRI images were fused for surgical planning. The accuracy of the neuronavigation system has proved to be good, and the safety of the procedure was enhanced. Therefore, neuronavigation and intraoperative MRI, though not available in all neurootological centres, should be considered useful tools in these challenging procedures.